Production of In-house ELISA Test Kit for Detection of Aflatoxin in Agricultural Commodities and Their Validations - Amara Chinaphuti; Chawalert Trikarunasawat; Arunsri Wongurai; Suparat Kositcharoenkul (Agriculture and Natural Resources, 2002)
A specific microtest plate enzyme immunoassay was developed in Thailand for the rapid detection of aflatoxin B1 (AFB1) using Polyclonal antibody against AFB1 . Percentage of the antibody cross reaction to AFB1, AFB2, AFG1 and AFG2 were 100, 21.4, 25.0 and 2.5% respectively. AFB1-HRP (Horseradish Peroxidase) conjugate was used as direct competitive test for AFB1 detection. The DOA- Aflatoxin ELISA Test Kit was produced for detection of both qualitative and quantitative results within 1 hr after sample preparation with the minimum of 0. 4 ppb per assay. There was no significant difference in detection efficiency of this test kit compared to traditional methods of minicolumn, TLC and HPLC. Moreover, the kit obtained 82-100% AFB1 recovery from the spike samples. Validation for the analysis of AFB1 in sample matrices was also tested using peanut extract which had the virtually identical curves to the standard. Detection efficiency of DOA–Aflatoxin ELISA test kit was not different from those imported from the USA and Italy.